AHMAD GHAZALI'S THOUGHTS IN THE BOOK OF ANFA' AL-WASĪLAH ON DETERMINING ‘ASR TIME PRAYER - Makhturoh, Siti; Shabir, Muslich; Izzuddin, Ahmad (Fakultas Syari'ah dan Hukum UIN Walisongo, 2022)
Ḥanafī's opinion differs from that of Al-Shāfi’ī in determining the entry of the time for the 'Asr prayer and the time for the Isha prayer. These two different determinations can be easily identified using the contextual method (calculation). The data needed in calculation is the high value of the Sun, so the thought of Ahmad Ghazali, an astronomer from Madura, explained about the height of the Sun based on two schools of thought. This provides a treasure of knowledge to someone in determining the entry of prayer times based on madhhab, just by looking at the clock. The type of method used in this study is qualitative field research with a descriptive approach, the aim is to describe Ahmad Ghazali's thoughts and to analyze in the field the given method. The results of the Anfa’ al-Wasīlah calculation with the addition of 1 in the irtifā’ formula is in accordance with the opinion of Al-Shāfi’ī, and an additional 2 in the irtifā’ formula according to the opinion of Ḥanafī, while from Ahmad Ghazali's opinion it states that the two early determinations of the time for the Asr prayer This is true, but it is more appropriate to use the ‘Aṣr Awwal time, because the ‘Aṣr Awwal opinion is supported by a number of scholars and strong arguments.